INISIATIF MASYARAKAT INDONESIA DI MASA AWAL PANDEMI COVID-19: SEBUAH UPAYA PEMBANGUNAN KESEHATAN - Marya Yenita Sitohang; Angga Sisca Rahadian; Puguh Prasetyoputra (Jurnal Kependudukan Indonesia, 2020)
The impact of the pandemic has influenced every aspect of people’s life. One of the positive impacts of the pandemic in Indonesia is the existence of the community initiative to prevent the COVID-19 spreading. This article aims to explore several initiatives coming from the society in relation to COVID-19 and the lesson learned for the society to have preparedness in facing health disasters. The data come from the 39 online news on the internet, the data was then analysed using a content analysis method. The authors found that Indonesian community initiative can be distinguished by two purposes i.e. to prevent the transmission of COVID-19 and to help the vulnerability group cope with the economic impact of COVID-19. Furthermore, mostly the initiative originally came from society without the intervention of the government. It is important to note that the collaboration between the government, both the centre and local, and the society should be strengthened.